Regulation of Extinction-Related Plasticity by Opioid Receptors in the Ventrolateral Periaqueductal Gray Matter - Parsons, Ryan; Gafford, Georgette M.; Helmstetter, Fred J. (Frontiers in Behavioral Neuroscience, 2010)
Recent work has led to a better understanding of the neural mechanisms underlying the extinction of Pavlovian fear conditioning. Long-term synaptic changes in the medial prefrontal cortex (mPFC) are critical for extinction learning, but very little is currently known about how the mPFC and other brain areas interact during extinction. The current study examined the effect of drugs that impair the extinction of fear conditioning on the activation of the extracellular-related kinase/mitogen-activated protein kinase (ERK/MAPK) in brain regions that likely participate in the consolidation of extinction learning. Inhibitors of opioid and N-methyl-D-aspartic acid (NMDA) receptors were applied to the ventrolateral periaqueductal gray matter (vlPAG) and amygdala shortly before extinction training. Results from these experiments show that blocking opioid receptors in the vlPAG prevented the formation of extinction memory, whereas NMDA receptor blockade had no effect. Conversely, blocking NMDA receptors in the amygdala disrupted the formation of fear extinction memory, but opioid receptor blockade in the same brain area did not. Subsequent experiments tested the effect of these drug treatments on the activation of the ERK/MAPK signaling pathway in various brain regions following extinction training. Only opioid receptor blockade in the vlPAG disrupted ERK phosphorylation in the mPFC and amygdala. These data support the idea that opiodergic signaling derived from the vlPAG affects plasticity across the brain circuit responsible for the formation of extinction memory.